THE APPLICABILITY OF THE PRINCIPLE OF IN DUBIO PRO SOCIETATE IN THE FIRST STAGE OF THE COURT OF THE JURY COURT IN THE CASE LAW OF THE STJ AND STF (CIPEEX, 2025)
The main objective of this research is to analyze the applicability of the principle "in dubio pro societate" in the first phase of the Jury Court before the understanding consolidated by the Superior Court of Justice and the Supreme Court. At first, it should be noted that the principle under study states that the judge, in case of doubt as to the defendant’s pronouncement, must decide in favor of the society, submitting the defendant to the rite of the Jury Court. However, the STF and STJ judges have too much mitigated the principle of "in dubio pro societate". This because its applicability directly affects the requirements of the defendant’s pronouncement to the Jury Court, they are: evidence of authorship and materiality of the crime against life. Even, the STF minister, Gilmar Mendes, stated that, having been in doubt, the principle "in dubio pro societate" can not justify the submission of accused to trial by the Jury Court. Moreover, as recommended by article 413 of the Code of Criminal Procedure, the decision of the accused to pronounce must be duly reasoned based on the requirements of evidence of materiality and authorship or participation in the crime. Therefore, if there are doubts about the basic requirements of pronunciation, it must be, in fact, the application of the principle of "in dubio pro reo", provided for in article 5, paragraph LVII, of the Federal Constitution, which favors the defendant in case of doubt.
Keywords: pronunciation; in dubio pro sociatate